Characterization of Microbial Dynamics and Volatile Metabolome Changes During Fermentation of Chambourcin Hybrid Grapes From Two Pennsylvania Regions - Wang, Hung Li; Hopfer, Helene; Cockburn, Darrell W.; Wee, Josephine (Frontiers in Microbiology, 2021)
Microbial diversity present on grapes in wineries, and throughout fermentation has been associated with important metabolites for final wine quality. Although microbiome-metabolome associations have been well characterized and could be used as indicators of wine quality, the impact of regionality on the microbiome and metabolome is not well known. Additionally, studies between microbiome and metabolome have been conducted on single species grape such as Vitis vinifera instead of other species and interspecific hybrids. Although the Pennsylvania wine industry is relatively young compared to California, the industry has been experiencing rapid growth over the past decade and is expected to continue to grow in the future. Pennsylvania’s climate of cold winters and high levels of rainfall throughout the growing season favors cultivation of interspecific hybrid grapes such as Vitis ssp. Chambourcin, one of the most commonly grown hybrid varieties in the state. Chambourcin is a prime candidate for studying the impact of regionality on microbiome-metabolome interactions as interspecific hybrid varieties could shape the future of winemaking. Here, we identify for the first time the regional distribution of microbial communities and their interactions with volatile metabolome during fermentation (0-20 days) by integrating high throughput Illumina sequencing (16S and ITS) and headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS). Analyzing 88 samples from nine wineries in the Central and East Pennsylvania regions, we observed high microbial diversity during early stages of fermentation (1-4 days) where wild yeasts, Starmerella and Aureobasidium and non-Oenococcus oeni bacteria, Sphingomonas, likely contribute to microbial terroir to the resulting wines. Furthermore, key differentiators between two regions in Pennsylvania, as identified by LEfSe analysis, include the fungal genera Cladosporium and Kazachstania and the bacterial genera Lactococcus and Microbacterium. Moreover, 29 volatile fermentation metabolites were discriminated significantly (VIP > 1) between the two regions as shown by Partial Least Squares-Discriminant Analysis (PLS-DA). Finally, Spearman’s correlation identified regional differences of microbial-metabolite associations throughout fermentation that could be used for targeted microbiome manipulation to improve wine quality and preserve regionality. In summary, these results demonstrate the microbial signatures during fermentation and differential microorganisms and metabolites further support impact of regionality on Chambourcin wines in Pennsylvania.